Factors associated with surgical site infections in emergency abdominal surgery - López-Crespo, Solansh (2018)
Introduction: Surgical wound infection (SWI) is the second more common cause of hospital infections. The aim of the present study was to determine associated factors to SWI occurrence in non-gynecological abdominal emergency operated patients at the “Hermillio Valdizán Medrano” regional hospital of Huanuco. Methods: It was carried out Case-Controls study in post-operated patients because of abdominal surgical emergency; records were used for all information. 184 patients participated; 92 cases and 92 controls. It was established a statistical association (p<0,05) with Chi2 for qualitative variables and Mann-Whitney U for quantitative variables. SPSS software was used. Results: 77,2% presented superficial SSI, 22,8% deep SSI and no one case of space organ SWI. Clean contaminated wound was the more frequent type (49,5%) and the more prevalent intervened organ was the hollow viscera (84,24%). The Body Mass Index (BMI) average was 24+-2, operating time average was 2,6+-1 hours. The disease time evolution average was 37 hours. Bivariated analysis showed statistical significance with hospital stay, operating time and Diabetes Mellitus. Conclusions: Statistical significant factors were hospital stay time, operating time and Diabetes Mellitus.